A statistical study of health literacy at a university in Jiangsu, China - Ye Xinmeng; Tian Si; Ren Fangrong (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
This paper aims to understand students' health literacy condition at a university in Jiangsu Province by determining possible influencing factors, and to give suggestions to improve health literacy education. A total of 165 first, second, and third-year students completed the Mandarin Health Literacy Scale (MHLS) questionnaire. Statistical analyses, including difference analysis, correlation analysis, regression analysis, and interactive analysis, were applied to examine the relationships between variables. The average score on the questionnaires was 45.78 out of a possible 50. The correlation coefficients between the Medical Service System and other sections were lower than those among the other sections. In addition, the high- and lowscoring groups on the Medication Information section had a significant interactive relationship with the Medical Service System in the Health Education Passage. In short, the health literacy of the students at this university was excellent. It can be concluded from the inter-section analysis that not only should their knowledge of the information in the Medical Service System section be strengthened, but Outpatient Department Conversation and Medication Information were key to improving overall health literacy.
Keywords: I19; I29; 330; Health literacy; health education of students; university students; Jiangsu; China